Pengaruh Kepemimpinan, Kompensasi, Motivasi Kerja, Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Trans Retail Indonesia (Carrefour) Pabelan Solo) - Zarkasih, Hikmatyar; , Dr. Erma Setiawati, MM.,CA (2016)
This study aims to determine the effect of leadership, compensation, motivation, organizational culture and work environment to employees performance at PT. Trans Retail Indonesia (Carrefour) Pabelan Solo. This research is a quantitative study, using the associative view the relationships between variables and measurement of population in this study were all employees of Carrefour Pabelan Solo. The sample used method Convinience Sampling. Obtained a sample of 150 questionnaires from employees of Carrefour Pabelan Solo. Data collection techniques used are Quetioner (questionnaire). Before the data is analyzed there should be testing of the data analysis requirements that the test instrument, the classical assumption test and multiple linear regression analysis. The results of this study indicated that organizational culture does not affect the performance of Carrefour employees, while the leadership, compensation, motivation, and work environment affect the performance of Carrefour employees. Keywords: Leadership, Compensation, Work Motivation, Organizational Culture, Work Environment and Employee Performance